Implementation of the Problem-Based Learning (PBL) Model to Improve Mathematics Learning Outcomes of Third-Grade Students - Roeth A.O.Najoan; Dwi Andriani Pamase; Mozes Yustus Legi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aimed to improve the mathematics learning outcomes of third-grade students at SD GP Berea Tondano through the implementation of the Problem-Based Learning (PBL) model. The research employed a Classroom Action Research (CAR) design consisting of two cycles, with each cycle involving the stages of planning, implementation, observation, and reflection. The subjects of the study were 15 third-grade students consisting of 7 boys and 8 girls. Data were collected through observation and learning outcome tests. The data were analyzed descriptively by calculating the percentage of students’ learning mastery in each cycle. The findings revealed that the implementation of the PBL model significantly improved students’ mathematics learning outcomes, particularly on the topic of area and perimeter of squares and rectangles. In Cycle I, the average student score was 62.33, with a learning mastery percentage of 46.67%, indicating that many students had not yet achieved the Minimum Mastery Criteria (KKM). After improvements were made in Cycle II through better classroom management, intensive guidance, and the use of multimedia learning resources, the average score increased to 96, with 100% learning mastery achieved. These results indicate that the Problem-Based Learning model effectively enhances students’ engagement, critical thinking, collaboration, and mathematics learning outcomes at the elementary school level.